VLF HISS OBSERVED AT SYOWA STATION, ANTARCTICA-II : Occurrence and Polarization of VLF Hiss During Disturbances - TANAKA, Yoshihito; 59238 (The Research Institute of Atmospherics, Nagoya University, 1972)
1972-03-30 The occurrence of VLF hiss is the greatest before the local magnetic midnight. Diurnal variations of occurrence probabilities are remarkably similar in the receiving frequencies of 5, 8, 12, 25 kHz. And they seem to coincide well with the diurnal pattern on the flux intensity of soft electrons (～l kev) precipitating over the station. The maximum energy is received near 10 kHz. There is a positive correlation between the occurrence of VLF hiss and K-index in geomagnetically undisturbed period, but the occurrences decrease during geomagnetic disturbances. The dependence of flux density on geomagnetic activity is also similar to the occurrence of VLF hiss. These facts clearly suggest that VLF hiss is generated in higher altitudes than the auroral ionosphere. The polarization at 12 kHz is independent of geomagnetic activity and the energy of VLF hiss, and it is roughly constant during a discrete VLF event appearing in geomagnetically undisturbed period. These results seem to suggest that wave couplings do not effectively occur in the lower ionosphere and the energy of VLF hiss is decided by the amount of precipitating soft electrons, and that VLF hiss propagates downward in the field aligned duct to an upper region of the auroral ionosphere. The distribution of (R/L) values observed is to be reasonably explained by the simultaneous arrival of multiple waves which independently come down with not so large angles of incidence roughly within the magnetic meridian plane. So, it is concluded that auroral hiss can not propagate to lower latitudes in the earth-ionosphere wave guide because of re-penetration into the auroral ionosphere and the inclination of incident angle toward higher latitude, so that auroral hiss is unique in the auroral zone and it is essentially different from low latitude type VLF hiss. departmental bulletin paper